2008
DOI: 10.1677/joe-08-0293
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetic and diabetic in vivo modification of circulating low-density lipoprotein attenuates its stimulatory effect on adrenal aldosterone and cortisol secretion

Abstract: Modification of low-density lipoprotein (LDL) and abnormal aldosterone and cortisol metabolism have been implicated in the pathogenesis of type 2 diabetes (DM2) and diabetic vascular disease. Since LDL serves as a major cholesterol source for adrenal steroidogenesis, we investigated whether LDL modification in prediabetic and diabetic subjects influences adrenocortical aldosterone and cortisol release. LDL was isolated from 30 subjects with normal glucose tolerance (NGT-LDL), 30 subjects with impaired glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In fact, the MultiEthnic Study of Atherosclerosis demonstrated an association between high oxLDL and the severity of coronary calcification [47]. Furthermore, enhanced circulating levels of oxLDL have been found in patients with impaired glucose tolerance [17] and type 2 diabetes [18]. In our study, VSMCs isolated from diabetic rats tended to become easily calcified.…”
Section: Involvement Of Ros In Oxldl-induced Osteogenic Transdifferensupporting
confidence: 55%
See 1 more Smart Citation
“…In fact, the MultiEthnic Study of Atherosclerosis demonstrated an association between high oxLDL and the severity of coronary calcification [47]. Furthermore, enhanced circulating levels of oxLDL have been found in patients with impaired glucose tolerance [17] and type 2 diabetes [18]. In our study, VSMCs isolated from diabetic rats tended to become easily calcified.…”
Section: Involvement Of Ros In Oxldl-induced Osteogenic Transdifferensupporting
confidence: 55%
“…In vascular cells, increased oxidative stress reduces the availability of nitric oxide, potentiates redox-sensitive signal transduction, and is able to convert LDL into oxidised (ox)LDL, the latter representing a pivotal established risk factor for cardiovascular disease. Interestingly, enhanced circulating levels of oxLDL have been found in patients with impaired glucose tolerance [17] and type 2 diabetes [18]. Furthermore, oxidative stress and oxidised lipids may promote osteogenic differentiation under appropriate conditions [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Elevations in inflammatory lipids such as LPC and long-chain fatty acids will induce endothelial dysfunction and eventually lead to hypertension [34]. Alterations in insulin secretion and other hormones such as aldosterone and catecholamines induced by these lipid changes will likewise affect blood pressure regulation [35][37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several mechanisms can be attributed for control in hyperglycemia by spironolactone and advanced studies are required to fi nd out specifi c mechanism. Impaired glucose tolerance and type 2 diabetes subjects are reported to exhibit enhanced circulating levels of oxidized LDL [ 27 ] . LDL modifi cation and overactivity of the RAAS has been related to the pathogenesis of type 2 diabetes [ 28 ] and its adverse cardiovascular consequences [ 27 ] .…”
mentioning
confidence: 99%
“…Impaired glucose tolerance and type 2 diabetes subjects are reported to exhibit enhanced circulating levels of oxidized LDL [ 27 ] . LDL modifi cation and overactivity of the RAAS has been related to the pathogenesis of type 2 diabetes [ 28 ] and its adverse cardiovascular consequences [ 27 ] . In the current investigation, diabetic rats exhibited dyslipidemia which was signifi cantly controlled by the spironolactone treatment.…”
mentioning
confidence: 99%